Development of ZnO/Al2O3 catalyst for reverse-water-gas-shift reaction of CAMERE (carbon dioxide hydrogenation to form methanol via a reverse-water-gas-shift reaction) process - Park, SW; Joo, OS; Jung, KD; Kim, H; Han, SH (ELSEVIER SCIENCE BV, 2001)
ZnO and ZnO/Al2O3 catalysts were studied for a reverse-water-gas-shift reaction (RWReaction). The catalytic activities depended on the compositions of Zn and Al at the temperature range of 673-973 K and GHSV of 15,000. The activities were close to the equilibrium conversion at temperatures above 873 K. The catalysts were characterized by using BET, TPR, XRD, SEM, and TEM. The ZnO/Al2O3 catalysts were mixtures of ZnO and ZnAl2O4 phases, and the particle size of the ZnO was strongly dependent on its composition in the ZnO/Al2O3 catalysts. ZnO/Al2O3 (Zn:Al = 1:1)catalyst has the smallest particle size of ZnO and its conversion of CO2 at 873 K and GHSV of 150,000 was 43%. The stability of ZnO/Al2O3 catalysts increased in the presence of the large particles of ZnO. Hence, ZnO/Al2O3 (Zn:Al = 4:1) catalyst was more stable than the ZnO/Al2O3 (Zn:Al = 1:1) catalyst. The conversion of CO2 on the ZnO/Al2O3 (Zn:Al = 1:1) catalyst decreased from 43 to 17% in 48 h. The ZnO in ZnO/Al2O3 catalysts was reduced to the Zn metal during the RWReaction, which contributed to the deactivation of the ZnO/Al2O3 catalysts, Meanwhile, the activity of ZnAl2O4 catalyst was stable for 100 h at 873 K and GHSV of 150,000. The ZnAl2O4 catalyst was developed for the RWReaction of the CAMERE (carbon dioxide hydrogenation to form methanol via a reverse-water-gas-shift reaction) process for methanol formation from CO2. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: REDUCTION; CU/ZNO